Сенсор на основе кантилеверных систем - Гетманенко, Н. Ю.; Рожицкий, Н. Н. (ХНУРЭ, 2010)
Инфекционные заболевания продолжают наносить весьма ощутимый вред здоровью людей во всем мире, в Украине - прежде всего. Высокая технологическая и антропогенная нагрузка на окружающую среду, политические и экономические кризисы, неблагоприятная демографическая ситуация, старение нации способствуют распространению инфекций. The general operation principle of atomic force microscope (AFM) is presented. The advantages of AFM for work with biological objects are considered. The results of biostructures investigation using AFM are presented. The operation scheme of biosensor based on cantilever systems is proposed. The recommendations concerning choice of detected response of sensor system depending on the sensor destination are evaluated.
Keywords: атомно-силовая микроскопия (АСМ); атомно-силовая микроскопия (АСМ); микрокантилеверный сенсор